2013
DOI: 10.1590/s1806-66902013000200018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in oriental tobacco (Nicotiana tabacum L.) by agro-morphological traits and simple sequence repeat markers

Abstract: -The objectives of this study were to assess genetic diversity and determine differences between several oriental tobacco genotypes by examining both agro-morphological traits and molecular markers. Simple lattice design with two replications was used to evaluate 100 oriental tobacco genotypes. Analysis of variance manifested that there is high level of genetic diversity in oriental-type tobaccos based on morphological traits including number of leaf, days to 50% flowering, leaf length, leaf width, leaf fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
0
11
3
7
Order By: Relevance
“…Oriental tobaccos have a different flavor, lower nicotine levels compared to commercial flue-cured Virginia and aircured Burley tobaccos and compared to Burley and bright tobaccos they also have lower tobacco specific nitrosamine (TSNA) levels. Therefore they are generally used in American blend type cigarettes by blending them with Virginia and Burley tobaccos (43). Precipitation and high humidity, especially during the harvest period, can delay maturation and leach down the resin and nicotine substances on the surface of the leaves.…”
Section: Nicotine Content Of Leavesmentioning
confidence: 99%
“…Oriental tobaccos have a different flavor, lower nicotine levels compared to commercial flue-cured Virginia and aircured Burley tobaccos and compared to Burley and bright tobaccos they also have lower tobacco specific nitrosamine (TSNA) levels. Therefore they are generally used in American blend type cigarettes by blending them with Virginia and Burley tobaccos (43). Precipitation and high humidity, especially during the harvest period, can delay maturation and leach down the resin and nicotine substances on the surface of the leaves.…”
Section: Nicotine Content Of Leavesmentioning
confidence: 99%
“…In 25 SSR loci, 135 flue-cured Virginia tobaccos had a total of 85 alleles (3.40 alleles per marker) (Ganesh et al, 2014). Darvishzadeh et al (2013) found two or three alleles per marker (mean: 2.69) in 100 tobacco genotypes, half of which originated from Iran. The results of the present study were in accordance with those of Darvishzadeh et al (2013) dealing with only one type of tobacco from a single region.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Tobaccos from the region are known by a variety of names in the literature. Among them are Samsun SM-1 (Aleksoska et al, 2014), Samsum (Bindler et al, 2007) Samsum Maden, TI 981 Samsun, Turkish Samsun (Fricano et al, 2012), Samsun (Tong et al, 2012), Samsun katenizi (Darvishzadeh et al, 2013), Samsun 959 and Samsun dere (Darvishzadeh et al, 2014). This variation results in a mixture of genotypes in the production area with different quality characteristics, thereby compromising the fine quality of Samsun oriental tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos outros trabalhos sobre divergência genética com base em características botânico-agronômicas foram realizados, demonstrando o seu potencial para estudar a divergência genética em diferentes espécies de plantas medicinais (CASTRO et al, 2005;MARIOT et al, 2009;CASTRO et al, 2011;BOLINA et al, 2013;DARVISHZADEH et al, 2013;MEZETTE et al, 2013).…”
Section: Divergência Genética Por Características Botânicoagronômicasunclassified